Volume 7A: Ocean Engineering 2019
DOI: 10.1115/omae2019-95769
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a High Accuracy Numerical Simulations of the Flow Around a Full Scale Ship

Abstract: The hydrodynamic performance of ships may be improved by the retrofit of Energy Saving Devices (ESDs). These devices are typically seen in the aft part of the ship hull and act by lowering the ship resistance, conditioning the fluid in front of the propeller and/or recovering energy from the rotational swirl of the fluid leaving the propeller. In the case of a retrofit of an existing ship no straight forward solution exists. In order to find a beneficial design that will improve hydrodynamic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Moreover, as the ship speed is increased, the difference also grows. This matches the pattern observed in the sinkage and trim curves for a ship, both theoretically [53,54] as well as numerically [55]. Turbulence modelling is also a source of error in the results presented herein.…”
Section: Spectral Analysis Of the Numerical Free Surfacesupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, as the ship speed is increased, the difference also grows. This matches the pattern observed in the sinkage and trim curves for a ship, both theoretically [53,54] as well as numerically [55]. Turbulence modelling is also a source of error in the results presented herein.…”
Section: Spectral Analysis Of the Numerical Free Surfacesupporting
confidence: 86%
“…More sophisticated modelling approaches, such as those accounting for transition or those resolving large parts of the turbulent kinetic energy spectrum, should be used to assess the sensitivity of the adopted approach to turbulence modelling. Recent studies have demonstrated that the latter approach can be highly beneficial in terms of accuracy [55].…”
Section: Ship Resistancementioning
confidence: 99%
“…Sistem propulsi terdiri dari sistem penggerak utama, sistem transmisi dan propulsor. Ketiga sistem ini merupakan satu kesatuan yang tidak dapat dianalisis secara terpisah saat merancang kapal (Pena, et al, 2019). Dampak yang ditimbulkan karena kesalahan dalam perencanaan sistem propulsi antara lain berkurangnya nilai ekonomis kapal, tidak tercapainya kecepatan yang direncanakan serta konsumsi bahan bakar yang tidak efisien (Andersson, et al, 2018).…”
Section: Sistem Propulsiunclassified
“…This work uses the Improved Delayed Detached Eddy Simulation (IDDES) turbulence modelling strategy and following the approach described in previous work (Pena et al, 2019;Pena et al, 2020).…”
Section: Turbulence Modelling Strategymentioning
confidence: 99%